Novel and uncommon antimicrobial resistance genes in livestock-associated methicillin-resistant Staphylococcus aureus - Kadlec, K.; Feßler, A.T.; Hauschild, T.; Schwarz, S. (Clinical microbiology and infection, 2012)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) isolates have been the subject of numerous studies during recent years. The characterization of such isolates has usually also included the determination of their resistance phenotypes and associated resistance genotypes. Analysis of the resistance genes present in LA-MRSA isolates has revealed a number of genes commonly found in S. aureus and coagulase-negative staphylococci of humans and animals. In addition, novel resistance genes and/or resistance genes that have been rarely detected in staphylococci so far have been encountered. These include the phenicol exporter gene fexA, the multiresistance gene cfr, the tetracycline resistance gene tet(L), the trimethoprim resistance gene dfrK, the macrolide–lincosamide–streptogramin B resistance gene erm(T), the lincosamide–streptogramin A–pleuromutilin resistance genes vga(C) and vga(E), and the apramycin resistance gene apmA. Most of these genes were located on multiresistance plasmids in LA-MRSA. The co-localization of these resistance genes with other resistance genes enables their co-selection and persistence. LA-MRSA can therefore act as a donor and a recipient of antimicrobial resistance genes within the Gram-positive gene pool.